(untitled) (Journal of Comparative Research in Anthropology and Sociology, 2025)
Romanian migration to the United States is shaped by a set of distinctive characteristics generated by socio-economic and cultural factors, which significantly influence the processes of adaptation and reconfiguration of social values within the migratory experience. This study aims to examine the social values underlying the emigration decisions of Romanians settled in American communities, drawing upon the motives identified through research and outlining the defining features of this phenomenon. The analysis is grounded in two major analytical perspectives: migration theories — represented by the push–pull model and Douglas Massey’s theory — and social value theories, as formulated by authors such as Thomas R. Rochon, Raymond Boudon, Rudolf Rezsohazy, Shalom H. Schwartz, and Ronald Inglehart. Methodologically, a thematic analysis was applied to a corpus of 18 semi-structured interviews conducted with members of Romanian communities in the American diaspora. The findings reveal four central dynamics: (1) family remains a core value, but its meaning shifts toward ensuring stability, intergenerational security, and access to opportunities unavailable in Romania; (2) work is reinterpreted through meritocracy and fairness, contrasting with corruption and nepotism in the country of origin; (3) education emerges as both a pathway to professional advancement and a mechanism for transmitting new values to younger generations; and (4) cultural identity, while preserved through language and traditions, is continuously renegotiated in interaction with American norms. A key contribution of the study is the identification of a value gap between Romanian migration to North America and to Europe: while European migration is often driven by short-term economic motives, U.S. migration is strongly associated with aspirational, identity-based goals centered on self-actualisation, dignity, and long-term integration. This research highlights migration as not merely a geographical relocation, but a profound process of value transformation and self-reconstruction, aligning individual trajectories with ideals of freedom, recognition, and social justice.